Korean Drama And Male Student (Phenomenology Analysis to Male Student of Islamic Boarding School KH Mas Mansur) - LARASATY, Anggitya Ornezza, Rinasari Kusuma, S.Sos, M.I.Kom, Fajar Junaedi, M.Si (2015)
Korean drama in the world of entertainment Indonesia is very popular with the teenagers. Not only women who love this drama, but also men. While viewing the men is synonymous with action movies or sports, some of them just love Korean dramas, as occurs in male students KH Mas Mansur Muhammadiyah Surakarta University. The analysis used is descriptive qualitative analysis with phenomenological approach by Edmund Hussel and Martin Heidegger. This analysis is a method to explain the phenomenon in its purity, which is created by the use of language, by constructing male student experience male of the Korean drama descriptively. The conclusion of this study is the male student of KH Mas Mansur who love Korean drama, do the patterns of cultural consumption as fans. Frequent consumption patterns are downloading videos of Korean dramas, or collect the soundtrack of the Korean drama. Other activities are buying clothes (fashion) used Korean artist. However, although such activities, if it is associated with the study of audiences, the male students is actually still at the stage of negotiating with Korean culture.